If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Hpt = 2pi Solving ptH = 2ip Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-2ip' to each side of the equation. -2ip + ptH = 2ip + -2ip Combine like terms: 2ip + -2ip = 0 -2ip + ptH = 0 Factor out the Greatest Common Factor (GCF), 'p'. p(-2i + tH) = 0Subproblem 1
Set the factor 'p' equal to zero and attempt to solve: Simplifying p = 0 Solving p = 0 Move all terms containing p to the left, all other terms to the right. Simplifying p = 0Subproblem 2
Set the factor '(-2i + tH)' equal to zero and attempt to solve: Simplifying -2i + tH = 0 Solving -2i + tH = 0 Move all terms containing p to the left, all other terms to the right. Add '2i' to each side of the equation. -2i + 2i + tH = 0 + 2i Combine like terms: -2i + 2i = 0 0 + tH = 0 + 2i tH = 0 + 2i Remove the zero: tH = 2i Add '-1tH' to each side of the equation. tH + -1tH = 2i + -1tH Combine like terms: tH + -1tH = 0 0 = 2i + -1tH Simplifying 0 = 2i + -1tH The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
p = {0}
| 7a-9b+36=0 | | Hot=2pi | | 6(3x+4+2y)= | | f(x)=2x^2+14x+23 | | 85(6)x=1020 | | f(x)=4X+2X^2+8X^3 | | 15(2a-1)=2a | | T-5/2=0 | | 223.4*7.5= | | 1x+29=4x-13 | | 28(4-2h)=3h | | X+29=4x-13 | | 25x^2-9y^2+300x-126y=-684 | | 14x+5y-8z=0 | | 1.666667x=10 | | (X-7)^2/3=2 | | 0.2b+0.1s=C | | 17=x/4 | | 17-x/4 | | -28(2-y)=3y | | 5x-2(x-5)=-2+5x+8 | | 4x-9=(5x-3)/3 | | 18=2/5m | | 8u/11=-3 | | 2cos(2x)+sinx=0 | | x-18= | | Q-60=85 | | 40x^2+36xy+25y^2=52 | | 9(3x-5)+4x-12= | | 4x-2y=13fory | | (6i)/(-2i) | | a=3.14rh |